Pasar di Jawa : pada masa Mataram kuna abad VIII-XI Masehi - Nastiti, Titi Surti (Jakarta : Pustaka Jaya, 2003)
History of ancient markets during Mataram Kingdom in Java from the 8th to 11th century
Includes bibliographical references (p. 167-176) and index
Keywords: Markets -- Java (Indonesia) -- History; Archaeology and history -- Indonesia -- Java; Java -- Antiquities